Criterion Validation of the Scales of Autonomy, Collaboration, Empathy, Problem-solving and Self-confidence of the 3SQ. Soft Skills Self-evaluation Questionnaire Adapted for Lower Secondary School - Stefano Scippo; Emiliane Rubat du Mérac (LED Edizioni Universitarie, 2021)
The Soft Skills Self-evaluation Questionnaire (3SQ, 41 items) was validated using the responses of 1216 Italian students attending the fourth and the fifth grade of upper secondary school (Lucisano & du Mérac, 2019a), demonstrating good psychometric properties (du Mérac & De Santis, 2020; du Mérac, Livi, & Lucisano, 2020). The adaptation of the 3SQ (40 items) for 8th-grade students was validated in Rome using the responses of 507 students, confirming the factorial structure, sufficient independence, and a good internal consistency (Cronbach alpha between .75 and .92 and 52.23% of the total variance explained). Here, we present the criterion-related validity of the five scales of the adapted 3SQ: Self-confidence, Autonomy, Problem-solving, Cooperation, Empathy. During a PhD research project (Scippo, 2021), these dimensions were also measured in Rome with other instruments, using a sample of 403 8th grade students. The analysis of the data confirms good reliability of the five scales (between .79 and .92), shows good indices of the confirmatory factor analysis of all the scales (RMSEA = .05, SRMR = .08), and reveals significant correlations (between .38 and .68) between the scales of the adapted 3SQ and the other scales measuring the same dimensions. In conclusion, this concurrent validity check reinforces the validity of the adapted 3SQ construct and, consequently, its usefulness for both research and guidance.